Clinical InvestigationsEvaluation of variation in dose of organs at risk in intracavitary brachytherapy of cervical cancer – a prospective study - Sharma, Brahmacharimayum Arunkumar; Singh, Tomcha; Singh, Jaichand (Journal of Contemporary Brachytherapy, 2011)
Purpose : The aim of this work was to evaluate the variation of dose in organs at risk (OARs) in fractionated high dose rate intracavitary brachytherapy (HDR-BT) for cervical cancer. Material and methods : A prospective study was carried out on 20 cervical cancer patients treated with fractionated (HDR-BT). International Commission on Radiation Units and Measurement (ICRU) bladder (bICRU) and rectum (rICRU) points were defined according to ICRU Report 38, using two orthogonal radiograph images taken by Simulator (Simulix HQ®) and prospectively kept to less than 80% of prescription dose to point A during real treatment planning process using the Plato Sunrise Treatment Planning System®. Results : The average variation of individuals in estimated doses of OARs in the inter fractional as well as in a single fraction were 2.4% and 0.7% of point A for rICRU, 4.3% and 1.6% for bICRU, and 0.8% & 0.2% for point B, whereas point A itself was found to be 1.6% & 0.6%. Conclusions : Average variation of the delivery of dose per fraction was found well within the recommended limit. The study observed smaller variation of doses to OARs which could present better reproducibility of geometry of (HDR-BT) applicators and its relative displacement with critical structures. Transportation of patient from simulator room to treatment room causes small uncertainties in delivery dose.